STRATEGI MENGATASI KESENJANGAN POTENSI ZAKAT DAN REALISASI PENGHIMPUNAN DANA ZAKAT DI BAZNAS KOTA MAKASSAR - Hidayat, Fahriza; Raehana, Syarifa; Bazith, Akhmad; Lawang, Hasanna; Subaedah (Program Studi Pendidikan Guru Sekolah Dasar FKIP Universitas Pasundan, 2026)
This study aims to analyze the strategies implemented by the National Amil Zakat Agency (BAZNAS) of Makassar City in addressing the gap between the potential and the actual realization of zakat collection, as well as to examine the realization of zakat fund collection that has been achieved. The research is based on the is-sue that the substantial zakat potential in Makassar City has not yet been fully re-alized through official zakat management institutions.This study employs a qualita-tive approach with a case study research design. Data were collected through in-depth interviews and documentation involving informants from BAZNAS, Zakat Collection Units (UPZ), and muzakki (zakat payers). Data analysis was conducted through data reduction, data presentation, and conclusion drawing.The findings indicate that the strategies implemented by BAZNAS Makassar City to address the gap between zakat potential and actual zakat collection include strengthening za-kat education and literacy among the community, enhancing the role of Zakat Col-lection Units (UPZ), utilizing digital-based payment services, and improving trans-parency in zakat fund management. The realization of zakat collection has shown positive growth from year to year; however, it remains below the existing zakat po-tential. The main obstacles identified include the limited public understanding of the importance of paying zakat through official institutions, the community's prefer-ence for distributing zakat directly to beneficiaries, and the suboptimal use of tech-nology at the UPZ level.This study concludes that the strategies implemented by BAZNAS Makassar City have been relatively effective; however, further optimiza-tion is needed through more intensive socialization programs, strengthening digital capacity, and expanding communication networks with the community to maximize zakat collection and bring it closer to its actual potential.